Incidence, risk factors and outcomes of urethral recurrence after radical cystectomy for bladder cancer: A systematic review and meta-analysis - Laukhtina, Ekaterina; Mori, Keiichiro; D Andrea, David; Moschini, Marco; Abufaraj, Mohammad; Soria, Francesco; Mari, Andrea; Krajewski, Wojciech; Albisinni, Simone; Teoh, Jeremy Yuen-Chun; Quhal, Fahad; Sari Motlagh, Reza; et al. (Urologic oncology, 2021)
We aimed to conduct a systematic review and meta-analysis assessing the incidence and risk factors of urethral recurrence (UR) as well as summarizing data on survival outcomes in patients with UR after radical cystectomy (RC) for bladder cancer. The MEDLINE and EMBASE databases were searched in February 2021 for studies of patients with UR after RC. Incidence and risk factors of UR were the primary endpoints. The secondary endpoint was survival outcomes in patients who experienced UR. Twenty-one studies, comprising 9,435 patients, were included in the quantitative synthesis. Orthotopic neobladder (ONB) diversion was associated with a decreased probability of UR compared to non-ONB (pooled OR: 0.44, 95% CI: 0.31-0.61, P < 0.001) and male patients had a significantly higher risk of UR compared to female patients (pooled OR: 3.16, 95% CI: 1.83-5.47, P < 0.001). Among risk factors, prostatic urethral or prostatic stromal involvement (pooled HR: 5.44, 95% CI: 3.58-8.26, P < 0.001; pooled HR: 5.90, 95% CI: 1.82-19.17, P = 0.003, respectively) and tumor multifocality (pooled HR: 2.97, 95% CI: 2.05-4.29, P < 0.001) were associated with worse urethral recurrence-free survival. Neither tumor stage (P = 0.63) nor CIS (P = 0.72) were associated with worse urethral recurrence-free survival. Patients with UR had a 5-year CSS that varied from 47% to 63% and an OS - from 40% to 74%; UR did not appear to be related to worse survival outcomes. Male patients treated with non-ONB diversion as well as patients with prostatic involvement and tumor multifocality seem to be at the highest risk of UR after RC. Risk-adjusted standardized surveillance protocols should be developed into clinical practice after RC.
Keywords: výsledek terapie; Risk factors; Urethral recurrence; Male; UR, RC; Risk Factors; lokální recidiva nádoru; nádory močového měchýře; Radical cystectomy; mužské pohlaví; incidence; Treatment Outcome; Neoplasm Recurrence, Local; lidé; ženské pohlaví; Humans; rizikové faktory; Cystectomy; cystektomie; Urinary Bladder Neoplasms; Female; Incidence